Designing a Risk Register Dashboard using the Human Centered Design Method to Increase the Risk Management Effectiveness - Alika Khairunnisa; Sheila Amalia Salma; Hadi Susanto (School of Industrial and System Engineering, Telkom University, 2024)
Every company must have uncertainties that can affect the company's performance. The risk is the result ofthe emergence of uncertainty. Risk management is a step that can be taken to measure the risks that exist inthe company. CV. XYZ, as a manufacturing company whose production floor involves both machines andhumans, has already implemented HIRARC methods in its risk management. CV. XYZ requires a riskregister dashboard as a tool for risk documentation and monitoring through real-time reports and annualreports. A dashboard is a tool used to analyze data and information. The rapid development of technologyhas led to improved solutions through information systems. The user interface risk register dashboard isdesigned using the Human-Centered Design (HCD) method, with steps to define user contextspecifications, user needs specifications, and user interface risk register dashboards. The design result ofthe user interface design risk register prototype with log-in page, menu form Risk update, mitigation andcontingency menus, risk database, and dashboard are divided into two categories, i.e., real-time report andannual report. User interface design can provide convenience and interaction to the user, and risk registrydashboard design can improve risk management efficiency with the presence of centralized and structuredrisk-related information, as well as facilitate risk evaluation, thus driving continuous improvement.